Multinodular and Vacuolating Neuronal Tumor–like Lesion of the Spinal Cord: Two Case Reports - Schollaert, Joris; Van der Planken, David; Mampaey, Sam; Breen, Matthew; Foo, Farng-Yang; Jain, Rajan; Van Goethem, Johan W.M. (American Journal of Neuroradiology, 2024)
We describe 2 cases of a spinal cord lesion with imaging features closely resembling those described in supratentorial multinodular and vacuolating neuronal tumor (MVNT) or infratentorial multinodular and vacuolating posterior fossa lesions of unknown significance. Multiple well-delineated nonenhancing T2-hyperintense intramedullary cystic ovoid nodules were visualized within the white matter of the spinal cord, including some immediately abutting the gray matter. No alterations in signal intensity or morphology were detected in a follow-up. Moreover, no relevant clinical symptoms attributable to the lesions were present. We describe these lesions as presumed MVNT, and we therefore use the term MVNT-like spinal cord lesions.MVNTmultinodular and vacuolating neuronal tumorMV-PLUSmultinodular and vacuolating posterior fossa lesions of unknown significanceUCulcerative colitis